POST DURAL PUNCTURE HEADACHE: A COMPARISON OF MIDLINE AND PARAMEDIAN APPROACH OF SPINAL ANESTHESIA - Nasir, Zeeshan; Mahboob, Saira; Mehmood, Tariq; Haider, Syed Zaheer (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the midline and paramedian approaches of spinal anesthesia in terms of incidence of Post Dural Puncture Headache among patients undergoing surgery.Study Design: Comparative prospective study.Place and Duration of Study: Department of Anesthesiology, Pakistan Naval Ship (PNS) Shifa Karachi, from Jan to June 2018.Methodology: After the approval of the hospital ethics committee, 214 (n=107 in each group) patients undergoing elective infra-umbilical surgery were included in our study. Group A were administered spinal anesthesia in sitting position via midline approach; whereas, paramedian approach was used in group B.Results: A total of 214 participants were studied. The two groups did not vary in demographic profile (p=0.017). The frequency of post-dural puncture headache was 2 (1.8%) in group B versus 10 (9.3%) in group A. There was no effect of American Society of Anesthesiologist physical status, gender, type of surgery, and age on the frequency of post dural puncture headache.Conclusion: There was a significantly lower frequency of post dural puncture headache in the paramedian approach for spinal anesthesia.